KESANTUNAN IMPERATIF PADA MASYARAKAT MADURA DI PASAR IKAN DESA KOTA KULON KABUPATEN BONDOWOSO - Retno Dyah Susilaningtyas; Bambang Wibisono; Budi Suyanto (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2017)
There is an imperative action on social interaction in the fish market. The interaction between traders, buyers, retailers, and porters. This acts dimension of politeness. Actual action are very bound by context. Using a pragmatic approach, this article examines the imperative action that apply to Madurese communities in the fish market in Kota kulon, Bondowoso, East Java. The data of this research is imperative speech acts spoken by the subject of research. Data is analytically analyzed according to the shape and scale of politeness. The result of the research shows that there are three ways to realize imperative action, that is using command sentence (imperative), declarative sentence, and interrogative. In detail there are six ways in realizing imperative action using imperative sentence, that is, using imperative sentences of command, solicitation, prohibition, request, order, decree, declarative, and interrogative sentence. The act of imperative using imperative sentence is considered polite if by superiors to subordinates. Subordinates to superiors can use imperative sentences if their relationships are very familiar and in informal situations. However, in general, the delivery of imperative actions using imperative sentences is considered less polite than the use of interrogative and declarative sentences. In addition, the use of particles of yah, ra, and ko in Madurese is used as an affirmation and measuring tool of politeness. Particle yah functioned to soften the speech, ra particles used when the opponent said to do two errors, and ko used when the opponent said to make mistakes repeatedly. In this study no particles found yah, ra, and ko used by subordinates to superiors.